Estudo metabolômico de espécies de Picramnia e reavaliação da classificação morfológica do gênero - Souza, Alicia Ludymilla Cardoso de (Universidade Federal de São Carlos, 2023)
The species Picramnia sellowii Planch. is a species of the order Picramniales, in the family Picramniaceae, with the vernacular name “Gogoia”. In reviews of the genus Picramnia and according to the APG IV reclassification, the chemotaxonomic marker of this family are the anthraquinones. Due to the complexity of these metabolites, metabolomics is the technique that investigates and assists in the identification or quantification in order to contribute not only to taxonomy, but to advances in the pharmaceutical industry from the search for active compounds in plants. Through tandem mass spectrometry, it is possible to accelerate the dereplication of molecules using molecular networks, before the subsequent isolation of compounds and then identify the potentially bioactive molecules. By means of tandem mass spectrometry, it is possible to accelerate the dereplication of molecules using molecular networks, before the subsequent isolation of the compounds and, subsequently, to identify potentially bioactive molecules. Still, citric canker is an important disease for citrus cultivation in several countries, such as Brazil and the United States, the two largest orange producers in the world. Caused by the bacterium Xanthomonas citri subsp. citri, the disease affects all commercially important citrus varieties and species. Chemical control of citrus canker in endemic areas is based exclusively on cupric bactericides. Cupric bactericides have no curative or systemic activity and are therefore applied in preventive management of citrus canker. Thus, metabolomics based on untargeted UHPLC-QTOF-MS/MS along with molecular networks was used to identify the classes of secondary metabolites present in P. sellowii. The library obtained from the analyses allowed the visualization of glycosylated flavonoids, catechins, chlorogenic acids, vitanolídeos, dimeric anthrones and quassinoids in Picramnia species. Thus, in order to search for new bactericides with low environmental toxicity, we first performed microbiological tests on P. sellowii extracts and fractions, evaluating their minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The Xanthomonas strains used throughout this study were resistant, tolerant and susceptible to copper. The results were promising with the fractions F3 and F2, the former at concentration of 125 µg mL-1 (MIC and MBC) against resistant, tolerant and susceptible strains, the latter at concentration of 250 µg mL-1 (MIC and MBC), 125 µg mL-1 and 250 µg mL-1 against resistant, tolerant and susceptible strains, respectively. Furthermore, this was the first report of the presence, isolation and structural identification of 5-O-caffeoylquinic acid (5-CQA) in the genus Picramnia and first profile performed by LC-MS/MS of the ethanolic extract of P. sellowii leaves, thus contributing to the chemotaxonomic knowledge of the species.
Metabolomic study of species of Picramnia and revaluation of the morphological classification of the genus.
Keywords: Metabolomic; Molecular network; Picramnia; Quassinoids; Chlorogenic acids; Xanthomonas; CIENCIAS EXATAS E DA TERRA::QUIMICA